Rheological Properties of Gluten as Function of Sodium Chloride During Heating - Helen C.D. Tuhumury (Universitas Pattimura, 2019)
Both rehydrated and fresh gluten samples were prepared in the presence and absence of NaCl during mixing and washing. The samples were subjected to the temperature sweep to determine the rheological properties of gluten during heating as a function of NaCl. In addition, the starch was added back to the gluten samples with and without NaCl to determine the effect of residual starch in the gluten network as influenced by NaCl. Gluten network formed in the presence of NaCl determine its rheological properties during heating. NaCl caused the enhanced hydrogen bonding in the formation of the gluten network during hydration, which may cause the onset in the sharp increase in G’ at higher temperature during heating. The delay of the sharp increase in the G’ value to higher temperature during heating is the results of the formation of the gluten network in the presence of NaCl not of the presence of the residual starch in the gluten network. Keywords: gluten, salts, small deformation rheology, starch, temperature sweep ABSTRAK Sampel gluten rehidrasi dan gluten yang baru dicuci disiapkan dengan dan tanpa NaCl selama proses pencampuran dan pencucian. Pengukuran reologi temperature sweep dilakukan untuk menentukan karakteristik reologi gluten selama proses pemanasan sebagai fungsi NaCl. Pati ditambahkan kembali pada gluten untuk proses rehidrasi dengan dan tanpa NaCl untuk menentukan pengaruh residu pati pada gluten seperti yang dipengaruhi oleh NaCl. Pembentukan jaringan gluten dengan NaCl selama pencampuran menentukan karakteristik reologinya selama proses pemanasan. NaCl meningkatkan ikatan hidrogen dalam pembentukan jaringan gluten selama hidrasi, yang dapat menyebabkan peningkatan G’ yang tinggi pada suhu yang lebih tinggi selama pemanasan. Penundaan peningkatan nilai G’ pada suhu yang lebih tinggi selama pemanasan sebagai akibat dari pembentukan jaringan gluten dengan NaCl bukan karena residu pati dalam jaringan gluten. Kata kunci: garam, gluten, pati, reologi deformasi kecil, temperature sweep